(untitled) (Research, Society and Development, 2023)
Introduction: Healthcare-Associated Infections are infections whose acquisition is related to a healthcare procedure or hospitalization, being classified as the most frequent adverse events in hospitalized patients, directly impacting the patient’s life and the hospital institution, representing serious health problems public across the world. Objective: To identify the importance of nursing in controlling hospital-acquired infections caused by HM, in light of patient safety measures in a hospital unit. Methods: This is an integrative review study in the databases indexed to the VHL, MEDLINE, LILACS and BDENF, using original and complete articles as inclusion criteria, published between 2017 and 2022, in English and Portuguese, and as exclusion criteria, monographs, duplicate articles and those unrelated to the topic. Results: This research comprises 20 articles, in which it was possible to see that the determining factors that put the patient at risk of contracting HAIs are hand hygiene. Final considerations: It is concluded that based on attentive and detailed surveillance by the team and nursing staff, the chances of reducing the risk of HAIs are promising. However, there is a need to use innovative strategic actions to reduce the risk of HAIs, as even in the midst of the pandemic situation in the world, infection prevention and control are still challenges for health institutions. Responsibility must be shared by all professionals, with correct hand hygiene as the main path.